The Penguin book of twentieth-century protest - MacArthur, Brian (Penguin Books, 1999)
"A riveting and colourful illumination of the history of our fearful century. All, or almost all, of the great causes are represented, and they are brought vividly to life by passion of the protestors' -- The Times Literary Supplement